2005
DOI: 10.1037/0096-3445.134.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Resource Slack and Propensity to Discount Delayed Investments of Time Versus Money.

Abstract: The authors demonstrate that people discount delayed outcomes as a result of perceived changes over time in supplies of slack. Slack is the perceived surplus of a given resource available to complete a focal task. The present research shows that, in general, people expect slack for time to be greater in the future than in the present. Typically, this expectation of growth of slack in the future is more pronounced for time than for money. In 7 experiments, the authors demonstrate that systematic temporal shifts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
273
5
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(287 citation statements)
references
References 40 publications
5
273
5
4
Order By: Relevance
“…Recent findings by Zauberman and Lynch (2005) also demonstrate the complex effects of time distance on optimism. They showed that people were more optimistic regarding the availability of both time and money resources in the future (in a month) compared with the present (today).…”
Section: Discussionmentioning
confidence: 93%
“…Recent findings by Zauberman and Lynch (2005) also demonstrate the complex effects of time distance on optimism. They showed that people were more optimistic regarding the availability of both time and money resources in the future (in a month) compared with the present (today).…”
Section: Discussionmentioning
confidence: 93%
“…Frederick et al (2002) provides a comprehensive review of the literature on intertemporal choice. Zauberman and Lynch (2005) show that decision makers discount time resources more than money. 22 These findings also address to a certain extent the concerns of Rubinstein (2003) over the psychological validity of hyperbolic discounting.…”
Section: Behavioral Regularitiesmentioning
confidence: 99%
“…This effect was accounted for by perceived resource constraint. Zauberman and Lynch (2005) demonstrated a similar pattern such that perceived abundance of resources led people to consider opportunity cost less while committing these resources for future tasks. Participants' perceived abundance of certain resources affected their temporal discounting of future investments of those resources.…”
Section: Resource Constraintsmentioning
confidence: 82%